The Case for Employee Referenda on Transformative Transactions As Shareholder Proposals - Matthew T. Bodie (Washington University Law Review, 2010)
This proposal would amend the bylaws to provide for a non-binding employee vote on any merger, acquisition, or other corporate combination on which the shareholders are also entitled to vote. The purpose of the referendum is to provide shareholders with information regarding the employees’ views on the transaction. Employees are in the midst of the day-to-day business of the company. Their repository of knowledge is a resource to be tapped, especially during the course of a transformative transaction. The referendum would provide a formal mechanism through which all employees could make their voices heard. It is hoped that the referendum would then spur increased interactions among the shareholders, the board, management, and employees on the wisdom of the transaction as well as the best ways to manage the company going forward.
Keywords: Corporate governance; Referendum; Stockholders' voting; Employee rights